Is There a Wage Payoff to Innovative Work Practices? - Michael J. Handel; Maury Gittleman (Levy Economics Institute of Bard College, 1999)
During the 1980s, wage inequality increased dramatically and the American economy lost many high wage, low- to medium-skill jobs, which had provided middle class incomes to less skilled workers. Increasingly, less skilled workers seemed restricted to low wage jobs lacking union or other institutional protections. Although "good" jobs for less skilled workers are unlikely to return in their previous form, a number of sociologists, economists, and industrial relations scholars have suggested that a new paradigm of work, often called "high performance," is emerging, which offers such workers more skilled jobs and higher wages. Using a unique national data set we find little evidence that high performance work systems are associated with higher wages.
Keywords: 330